SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/113432-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Performance Surfactants for Difficult Oils

Abstract: Several novel surfactants have shown excellent performance in tests using several crude oils that have properties, such as high wax content, that make high oil recovery with surfactants very difficult. High carbon-number, internal olefin sulfonates, when used with appropriate co-surfactants, co-solvents and alkali, produced the type of phase behavior and ultra-low interfacial tension needed for almost 100% oil recovery from laboratory core experiments. These surfactants could be used at both low and high tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…Because the sulfonate group is added at different points along the hydrocarbon chain during synthesis, internal olefin sulfonate (IOS) surfactants consist of species with different branching. Results of laboratory studies of IOS phase behavior at high temperatures have recently been presented (Barnes et al, 2008;Zhao et al, 2008). Hydrocarbon chain lengths ranged from C 15 -C 18 to C 24 -C 28 .…”
Section: Surfactant Requirements and Structuresmentioning
confidence: 99%
“…Because the sulfonate group is added at different points along the hydrocarbon chain during synthesis, internal olefin sulfonate (IOS) surfactants consist of species with different branching. Results of laboratory studies of IOS phase behavior at high temperatures have recently been presented (Barnes et al, 2008;Zhao et al, 2008). Hydrocarbon chain lengths ranged from C 15 -C 18 to C 24 -C 28 .…”
Section: Surfactant Requirements and Structuresmentioning
confidence: 99%
“…It was also found that high molecular weight internal olefin sulfonate (IOS) surfactants perform exceptionally well with the difficult oils in terms of providing efficient micro-emulsion compared to many other types of surfactants. In oil/brine/surfactant mixtures, IOS surfactants do not exhibit the tendency to form the liquid crystals, gels and ordered structures in spite of lacking branching (Barnes, Dirkzwager, Smit, & Smit, 2010;Zhao et al, 2008). Phase behaviour tests include the aqueous stability test, salinity scan and oil scan.…”
Section: Surfactant Phase Behaviourmentioning
confidence: 99%
“…In the comment/remark column, we have summarized significant remarks, observations, or criticism pertaining to the specific reference or article. In short the following useful information could be obtained from Table 1: • Anionic surfactants were often employed in in situ prepared microemulsions techniques and often produce promising results (Glinsmann, 1979;Bae and Petrick, 1981;Gupta, 1982;Sanz and Pope, 1995;Austad and Taugbøl, 1995a;Austad and Taugbøl, 1995b;Taugbøl et al, 1995;Austad et al, 1997;Levitt et al, 2006;Bouabboune et al, 2006;Zhao et al, 2008). These surfactants could significantly reduce the IFT of the fluid system tested.…”
Section: In Situ Prepared Microemulsion Flooding Workmentioning
confidence: 99%
“…The flooding was stable and effective even at high temperature and high salinity (Iglauer et al, 2009;Wang et al, 2010;Dwarakanath et al, 2008). • Many cosurfactant(s) have been used with various surfactants to assist the surfactant to immensely lower the IFT and increase the efficiency of oil displacement (Glinsmann, 1979;Bae and Petrick, 1981;Kraft and Pusch, 1982;Gupta, 1982;Bragg et al, 1982;Nelson, 1983;Levitt et al, 2006;Bouabboune et al, 2006;Zhao et al, 2008;Dwarakanath et al, 2008;Iglauer et al, 2009) First, the mobility of the micellar fluid was too high. Therefore, early sulfonate breakthrough was observed.…”
Section: In Situ Prepared Microemulsion Flooding Workmentioning
confidence: 99%
See 1 more Smart Citation